2018
DOI: 10.1007/s12012-018-9469-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of Simulated Smog Atmospheres Affects Cardiac Function in Mice

Abstract: The health effects of individual criteria air pollutants have been well investigated. However, little is known about the health effects of air pollutant mixtures that more realistically represent environmental exposures. The present study was designed to evaluate the cardiac effects of inhaled simulated smog atmospheres (SA) generated from the photochemistry of either gasoline and isoprene (SA-G) or isoprene (SA-Is) in mice. Four-month-old female mice were exposed for 4 h to filtered air (FA), SAG , or SA-Is. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The study of the isolated heart is used in several types of tests being extremely useful in the translational evaluation of these pharmacological tests [32,33]. According to Tong et al [34], heart retrograde perfusion models are ex vivo methods of clinical relevance for the study of myocardial infarction to evaluate function and injury.…”
Section: Discussionmentioning
confidence: 99%
“…The study of the isolated heart is used in several types of tests being extremely useful in the translational evaluation of these pharmacological tests [32,33]. According to Tong et al [34], heart retrograde perfusion models are ex vivo methods of clinical relevance for the study of myocardial infarction to evaluate function and injury.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical study Madden et al (Madden et al 2014) showed that the combination of O 3 and DE co-exposure produced greater than additive of effects of O 3 and DE on lung function decrements in healthy adults, suggesting that a potential interaction between the gaseous and particulate pollutants inducing greater than additive effects. In addition, animal studies demonstrated that the cardiovascular effects of atmosphere mixtures exposure were dominated by the gaseous components (McIntosh-Kastrinsky et al 2013, Tong et al 2018, Hazari et al 2018). However, Kurhanewicz et al (Kurhanewicz et al 2014) found that co-exposure of O 3 with fine or ultrafine PM produced varied cardiac responses, suggesting that cardiovascular effects of particle-gas co-exposures are not simply additive or even generalizable.…”
Section: Discussionmentioning
confidence: 99%